Histoire comparée de l’action politique au sein des communautés italiennes au Québec et en Suisse de 1945 à 1985 - Guerrera, Marco (Université de Montréal, 2003)
Keywords: Italiens

Fascisme et communauté italienne de Montréal d'après L'Italia Nuova - Laplante, Jacinthe (Université de Sherbrooke, 2008)
Keywords: Idéologies; Italiens

Réminiscences italiennes - Létourneau, Isabelle (Continuité, 2001)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal, le cas des Portugais, des Maghrébins et des Italiens - Paiement, Isabelle (Université du Québec à Montréal, 2000)
Keywords: Italiens; Maghrébins; Portugais

La communauté italienne de Montréal en 1901 - Tonietto, Manon (Université du Québec à Montréal, 2004)
Keywords: Italiens; Quartiers; Saint-Jacques; Saint-Laurent (quartier)

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

The Influence of Culture on Pro-Environmental Activities: Comparing English, French and Italian Canadians - Qian, Zhonglian Cindy (Université Concordia, 2001)
Keywords: Italiens

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Actor or Victim? Mario Duliani and His Internment Narrative - Perin, Roberto (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Guerre; Italiens

The Internment of Italian Canadians - Bruti Liberati, Luigi (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Italiens; Prisons

Italian Immigrant Women and Literacy: A Case Study - Constantino, Patricia (Université Concordia, 2001)
Keywords: Femmes; Italiens

From Acculturation to Integration. The Political Participation of Montréal's ltalian-Canadian Community in an Urban Context (1945-1990) - Ricci, Amanda (Université de Montréal, 2009)
Keywords: Féminisme; Italiens

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Une communauté en transition: la Petite Italie de Montréal - Del Balso, Michael (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Cultivating Heroes: From Dante and Caboto to Mussolini, the Public Art of Montreal's Italians in the 1920s-1930s - Carlevaris, Anna Maria (Université Concordia, 2004)
Keywords: Italiens; Monuments; Peinture; Sculpture

Women and Ethnic Language Maintenance: A Study of Italian Immigrant Family Triads in Saint-Léonard, Montréal - Venditti, Rosa L. (Université Concordia, 2003)
Keywords: Italiens; Langue; Quartiers; Saint-Léonard

La crise de Saint-Léonard dans la presse montréalaise, 1968-1969 - Chikli, Christophe (Université de Sherbrooke, 2006)
Keywords: Devoir (Le); Italiens; Langue; Montreal Gazette; Montreal Star; Presse (La); Saint-Léonard (crise de)